2012
DOI: 10.1002/pen.23334
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of injected polypropylene/clay nanocomposite materials

Abstract: Polypropylene (PP) clay nanocomposites were injection‐molded using two different coupling agents based on maleic anhydride‐grafted PP (MA‐g‐PP) and two clay loadings. The morphological aspects of these materials were studied by depth profiling. Molecular chain and clay orientations were characterized using attenuated total reflectance‐infrared analysis and transmission electron microscopy (TEM). Both clay platelets and PP molecular chain orientations were found to decrease from the surface toward the core of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
1
1
Order By: Relevance
“…ey attributed this high gloss surface to the amorphous phase, which completely wrapped all crystalline phases on the surface; finally, the surface presented a pure and uniform amorphous phase. However, this conclusion differs from the observations of other researchers [17,21,31] who indicated that the surface of the PP sample is composed of both crystalline and amorphous phases. Another researcher (Wang et al [35]) pointed out that, for the virgin PP, the surface gloss exhibited a different trend: instead of increasing, it tended to decrease as the cavity surface temperature continued to rise after reaching 110°C.…”
Section: Relationship Between Microstructure and Surface Glosscontrasting
confidence: 99%
See 1 more Smart Citation
“…ey attributed this high gloss surface to the amorphous phase, which completely wrapped all crystalline phases on the surface; finally, the surface presented a pure and uniform amorphous phase. However, this conclusion differs from the observations of other researchers [17,21,31] who indicated that the surface of the PP sample is composed of both crystalline and amorphous phases. Another researcher (Wang et al [35]) pointed out that, for the virgin PP, the surface gloss exhibited a different trend: instead of increasing, it tended to decrease as the cavity surface temperature continued to rise after reaching 110°C.…”
Section: Relationship Between Microstructure and Surface Glosscontrasting
confidence: 99%
“…e statistical results of crystallinity in each layer in all samples are shown in Figure 8. e inner crystallization variation trend in the CIM sample is the same as the study result obtained by Salah et al [31]. And the crystallinity in each layer in the RHCM samples is higher than that in the CIM sample; furthermore, the crystallinity in all layers increases continuously as the cavity surface temperature increases.…”
Section: Effect Of Rhcm Process On Crystallinity In the Microstructursupporting
confidence: 83%
“…Around 0.2 mm virgin PP from the walls nucleated and it is interpreted that it solidified virgin PP tends to adhere on the wall during 3.06 s injection period. It is mentioned that the cooling rate, temperature gradient, shear condition, pressure distribution, and many other injection parameters strongly affect the distribution of crystallization behaviour of PP, frozen, and the surface quality and mechanical properties of plastic parts [17].…”
Section: Resultsmentioning
confidence: 99%